Active surveillance for localized prostate cancer: update of a prospective single-center cohort. (2nd January 2018) - Thostrup, Mathias; Thomsen, Frederik B.; Iversen, Peter; Brasso, Klaus
Abstract: Objective: The purpose of active surveillance (AS) is to reduce overtreatment of men with localized prostate cancer (PCa) without compromising survival. The objective of this study was to update a large Scandinavian single-center AS cohort. Furthermore, the use of curative treatment and subsequent risk of biochemical recurrence were investigated and compared in men with very low-risk, low-risk and intermediate-risk PCa in the cohort. Materials and methods: In total, 451 men were followed on AS and monitored with prostate-specific antigen (PSA) tests, digital rectal examinations and rebiopsies. Recommendation of curative treatment was based on protocolled and predefined risk of progression criteria. Biochemical recurrence was defined as PSA ≥0.2 ng/ml after radical prostatectomy and PSA nadir +2 ng/ml after radiotherapy. Results: Altogether, 34% were defined with very low-risk PCa, 40% with low-risk PCa and 24% with intermediate-risk PCa. The median follow-up was 5.1 years. The estimated 5 year curatively intended treatment-free survival was 60.5% [95% confidence interval (CI) 54.8–66.2%], with no statistically significant difference between men with very low-risk, low-risk or intermediate-risk PCa. The 5 year biochemical recurrence-free survival was 92.3% (95% CI 87.4–97.2), again with no difference between men with very low-risk, low-risk and intermediate-risk PCa. Conclusion: AS for very low- to low-risk localized PCa is feasible and safe within the short to intermediate time frame. Men with intermediate-risk PCa had the same risk of undergoing curative treatment as men with low-risk PCa, without compromising biochemical recurrence-free survival.